2021
DOI: 10.1097/nmd.0000000000001427
|View full text |Cite
|
Sign up to set email alerts
|

Public Stigma of Prolonged Grief Disorder

Abstract: Prolonged grief disorder's (PGD's) recent recognition as a psychiatric diagnosis has elicited concerns about stigmatization. Although prior research demonstrated that PGD elicits public stigma, moderators of this effect are unclear, and the effect requires replication in an English-speaking population. Therefore, we investigated the effects of PGD, sex of the bereaved, and death expectedness on public stigma toward bereaved persons. We randomly assigned 195 Australian adults (77% female; mean age, 35.7 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A series of vignette-based experimental studies conducted in the Netherlands, Germany and Australia has demonstrated that the general public stigmatizes people with PGD symptoms and diagnoses (vs people with non-clinical grief) more ( Dennis et al, 2022 ; Eisma, 2018 ; Eisma et al, 2019 ; Gonschor et al, 2020 ). That is, people with PGD are attributed more negative traits and elicit more negative emotions and a greater desire for social distance.…”
Section: Pgd In Icd -11 and Dsm ...mentioning
confidence: 99%
“…A series of vignette-based experimental studies conducted in the Netherlands, Germany and Australia has demonstrated that the general public stigmatizes people with PGD symptoms and diagnoses (vs people with non-clinical grief) more ( Dennis et al, 2022 ; Eisma, 2018 ; Eisma et al, 2019 ; Gonschor et al, 2020 ). That is, people with PGD are attributed more negative traits and elicit more negative emotions and a greater desire for social distance.…”
Section: Pgd In Icd -11 and Dsm ...mentioning
confidence: 99%
“…However, acculturation literature has shown that abandoning home culture and completely assimilating to the host culture is neither beneficial to mental health nor realistic, especially for highly enculturated, adult immigrants (Jang et al, 2007; Yoon et al, 2013). Moreover, grief is a natural process (vs. pathology) of migration (Dennis et al, 2022). Accordingly, clients may benefit from working on processing their grief, rather than simply attempting to reduce migratory grief.…”
Section: Discussionmentioning
confidence: 99%
“…До досліджуваних факторів ризику розвитку РПГ належать жіноча стать, низький рівень соціально-економічного благополуччя, висока інтенсивність симптомів на ранніх етапах горювання, наявність депресивних або тривожних розладів в анамнезі, втрата дитини або партнера, раптовість та непередбачуваність смерті близької людини, підтримка оточення протягом горювання [24][25][26][27][28].…”
Section: фактори ризику рпгunclassified